TINGKAT PENDIDIKAN, PENGALAMAN KERJA, KOMITMEN PROFESIONAL DAN DISIPLIN KERJA AUDITOR PADA RENTANG WAKTU PENYELESAIAN AUDIT - Wicaksana, Made; Budiartha, Ketut (E-Jurnal Akuntansi; Vol 13 No 2 (2015), 2015)
The range of audit completion time can affect the timeliness of information on the results of the audit. Timeliness of financial reporting is an essential element for adequate records of financial statements. This study aimed to determine the effect of education level auditors, auditors work experience, professional commitment and discipline auditors on audit completion time span in the public accounting firm of Bali province. The study population was all auditors who work in public accounting firm that is registered in the Public Accountants Association of Bali Indonesia samples obtained in 2014 amounted to 63. The results of this study indicate that the educational level variable auditors, auditors work experience, professional commitment and discipline auditors auditors effect on the audit completion time span.
Keywords: span of completion of the audit, the auditor' s level of education, work experience of auditors, professional commitment and discipline auditors.